Factors influencing risky single occasion drinking in Canada and policy implications - Ellen Rafferty; William Ian Andrew Bonner; Jillian Code; Keely McBride; Mustafa Andkhoie; Richa Tikoo; Stephanie McClean; Colleen Dell; Michael Szafron; Marwa Farag (BMC, 2017)
Abstract Background Misuse of alcohol, including single risky occasion drinking (RSOD) is associated with a number of health, social and economic consequences. While research demonstrates that many factors contribute to individuals' drinking practices, little is known about risk factors that contribute to RSOD in the Canadian population. The objectives of this study are to examine the patterns of RSOD in Canada, to identify factors associated with RSOD, and to explore policy implications. Methods The Canadian Community Health Survey (CCHS) 2009-2010 annual component was used to conduct all the analyses in this paper. We used two models: (1) a binary logistic regression model, and (2) a multinomial logistic regression model, to identify factors that were significantly associated with our dependent variables, RSOD engagement and frequency of RSOD, respectively. Results Daily smokers were 6.20 times more likely to engage in frequent RSOD than those who never smoke. Males were 4.69 times more likely to engage in risky RSOD. We also found significant associations between the frequency of RSOD and Province/Territory of residence, income and education, marital status and perceived health status. Finally, stress was associated with engaging in infrequent RSOD. Conclusions Our finding associating daily smoking with risk alcohol intake specifically suggests the possibility of combining public health interventions for both. The study findings also indicate that education is a protective factor, further supporting the role of education as a major determinant of health. The significant provincial variation we found also point to the need to study this issue further and understand the links between provincial level policies and RSOD.